Hydrological impact of war-induced deforestation in the Mekong Basin - Lacombe, Guillaume; Pierret, Alain (Wiley, 2013)
The Vietnam War played a decisive role in the pre-1990s deforestation of the lower Mekong Basin, which in turn likely influenced regional broad-scale hydrology. This note presents and discusses new analyses that strengthen this thesis. Although concurrent overestimation of discharge and underestimation of rainfall, a couple of years after bombing climaxed in the early 1970s, could theoretically explain the sharp rise in water yield previously attributed to bomb-induced deforestation, new observations suggest that bombing has durably modified the landscape: by 2002, degraded forests still largely overlapped with areas heavily bombed 30 years earlier. This corroborates observed long-term hydrological changes and suggests that warfare-induced deforestation has more profound and durable hydrological effects than previously thought.